Strategi Branding Destinasi Wisata Berbasis Kearifan Lokal Melalui Program-Progran Desa Wisata di Desa Selamanik Kecamatan Cipaku Kabupaten Ciamis - Puji Lestari; Arie Budiawan; Sari Nurhayati; Yoga Gustiadi; Ibah Muhammad Misbahudin (Universitas 17 Agustus 1945, 2025)
Selamanik Village, Cipaku District, Ciamis Regency, has developed various tourist village programs to increase its attractiveness as a leading destination. This research aims to analyze local wisdom-based destination branding strategies implemented through tourism programs in this village. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews and documentation studies. The research results show that tourism programs such as Live-In Selamanik, Kampung Jaya Wijaya Innovation, and the potential development of sunflowers currently underway are expected to be the main elements in building the image of the village as a tourism destination based on education, culture and Agrotourism in accordance with local wisdom demonstrated. The branding strategy implemented includes the use of social media, strengthening local identity through tourism icons, and active community involvement in tourism management. Meanwhile, the competitiveness of tourist villages is increased through diversifying outdoor activities, improving facilities, and developing tourism experiences based on community participation. This research concludes that the success of the Selamanik Tourism Village branding strategy is very dependent on the synergy between the village government, community and tourists. The recommendations given include increasing digital promotions, strengthening collaboration with tourism stakeholders, as well as sustainable innovation in local wisdom-based tourism programs.